Photo-induced oxide-doped glass, method of manufacture and colored glass article

CN122977696APending Publication Date: 2026-10-27SHENZHEN XINQIBIN TECHNOLOGY DEVELOPMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611235685.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

此方法中,金属纳米颗粒聚集处与非聚集处会形成明显的异质区域,影响其力学性能;金属纳米颗粒的局部富集还会干扰离子交换中碱金属离子的扩散路径与浓度分布,造成化学强化层深度与应力值不均,影响强化效果

Benefits of technology

[0069]本申请在不引入卤化物和金属纳米颗粒的条件下,通过将Sb2O3、Ag2O和CeO2按特定的质量百分数引入光诱导氧化物掺杂玻璃中,这三种氧化物与其他组分的协同作用,可以形成玻璃的光谱特性与显色性,从而可以采用光诱导工艺实现显色,得到具有定制化图案或分区色彩的显色玻璃制品。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977696A_ABST
    Figure CN122977696A_ABST
Patent Text Reader

Abstract

The application relates to a photo-induced oxide-doped glass, a preparation method and a color-developed glass product. The photo-induced oxide-doped glass comprises the following components in percentage by mass: 70.00%-75.00% of SiO2, 5.00%-8.00% of Al2O3, 9.00%-12.00% of Li2O, 1.50%-3.20% of Na2O, 0%-4.00% of K2O, 0%-0.60% of B2O3, 3.00%-5.00% of ZrO2, 1.50%-2.50% of P2O5, 0.30%-0.50% of Sb2O3, 0.05%-0.30% of Ag2O and 0.10%-0.30% of CeO2. The application can not introduce halides and metal nanoparticles, by introducing specific percentage by mass of Sb2O3, Ag2O and CeO2, which can form the spectral characteristics and color development of the glass in cooperation with other components, so that the color development can be realized by using a photo-induced process, and a color-developed glass product with customized patterns or partitioned colors is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of glass manufacturing technology, and relates to a photoinduced color-developing glass, and more particularly to a photoinduced oxide-doped glass, its preparation method, and color-developing glass products. Background Technology

[0002] Glass products are widely used in various consumer electronics devices, serving as exterior components for portable electronic devices such as smartphone back covers, tablets, and smartwatch covers. Therefore, glass products not only need excellent mechanical properties but also require higher standards for aesthetic appeal. The market urgently needs glass products with customizable patterns, zoned colors, and continuous gradient colors. Currently, coloring schemes for electronic glass mainly fall into two categories: traditional integral ion coloring and film-based processes. The former is not economically viable for mass production and cannot be shaped; the latter lacks the color and luster of the original glass.

[0003] Photoinduced color-changing glass, through the photochemical action of doped oxides, can achieve customized shapes for color development or patterns by spectrally modulating its optical properties after molding, and has the potential to be transferred to electronic back cover glass technology. However, due to the different glass system, traditional photoinduced color-changing glass is difficult to adapt to the scratch-resistant, shatter-resistant, and ion-strengthened properties of electronic glass.

[0004] CN120943529A discloses a colored photosensitive microcrystalline glass, its preparation method, and its applications. This method achieves colored photosensitive microcrystalline glass with both color-developing function and photosensitive microcrystallization characteristics through compositional gradient design and multi-stage heat treatment. However, this method contains halides such as fluorides and bromides, which are highly corrosive during the high-temperature melting process of glass. These halides severely corrode mainstream production equipment such as platinum crucibles and industrial furnaces, significantly increasing equipment wear and production costs. Furthermore, halides are prone to volatilization at high temperatures, causing fluctuations in glass composition, leading to poor color uniformity and long-term stability, and also generating harmful gases, posing environmental hazards.

[0005] CN109311732A discloses a component based on multicolor photosensitive glass and its manufacturing method. This method utilizes metal nanoparticles (Au / Ag / Cu) within an aluminosilicate glass system, achieving multicolor patterning through size control. However, this method results in significant heterogeneous regions between aggregated and non-aggregated areas of the metal nanoparticles, affecting their mechanical properties. Furthermore, localized enrichment of the metal nanoparticles interferes with the diffusion path and concentration distribution of alkali metal ions during ion exchange, leading to uneven depth and stress values ​​in the chemically strengthened layer and impacting the strengthening effect.

[0006] Therefore, how to develop a new photo-induced color-developing glass and its preparation method is an urgent problem to be solved in this field. Summary of the Invention

[0007] In view of the shortcomings of the existing technology, the purpose of this application is to provide a photoinduced oxide-doped glass and a method for preparing the same.

[0008] To achieve this objective, the present application adopts the following technical solution:

[0009] In a first aspect, this application provides a photoinduced oxide-doped glass, which, by mass percentage, comprises the following components: 70.00%~75.00% SiO2, 5.00%~8.00% Al2O3, 9.00%~12.00% Li2O, 1.50%~3.20% Na2O, 0%~4.00% K2O, 0%~0.60% B2O3, 3.00%~5.00% ZrO2, 1.50%~2.50% P2O5, 0.30%~0.50% Sb2O3, 0.05%~0.30% Ag2O, and 0.10%~0.30% CeO2.

[0010] For example, in photoinduced oxide-doped glass, the mass percentage of SiO2 can be 70.00%, 70.25%, 71.00%, 71.25%, 72.00%, 72.20%, 73.00%, 73.10%, 73.19%, 74.00%, 74.35%, or 75.00%, etc.; the mass percentage of Al2O3 can be 5.00%, 5.20%, 5.50%, 6.00%, 6.20%, 7.00%, 7.66%, or 8.00%, etc.; and the mass percentage of Li2O can be 9.00%. The mass percentages of Na₂O can be 1.50%, 1.55%, 1.60%, 1.80%, 1.98%, 2.00%, 2.20%, 2.28%, 2.50%, 2.80%, 3.00%, or 3.20%, etc.; the mass percentages of K₂O can be 0%, 0.50%, 1.00%, 1.50%, 2.00%, 2.5%, etc. The mass percentages of B2O3 can be 0%, 0.10%, 0.20%, 0.30%, 0.40%, 0.45%, 0.50%, or 0.60%, etc.; the mass percentages of ZrO2 can be 3.00%, 3.20%, 3.50%, 3.80%, 4.00%, 4.20%, 4.50%, 4.80%, or 5.00%, etc.; the mass percentages of P2O5 can be 1.50%, 1.80%, 2.00%, 2.20%, 2.22%, etc. The mass percentages of Sb2O3 can be 0.30%, 0.35%, 0.40%, 0.45%, or 0.50%, etc.; the mass percentages of Ag2O can be 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.27%, 0.28%, or 0.30%, etc.; the mass percentages of CeO2 can be 0.10%, 0.15%, 0.20%, 0.22%, 0.25%, 0.27%, 0.28%, or 0.30%, etc.

[0011] This application introduces Sb2O3, Ag2O, and CeO2 into photoinduced oxide-doped glass at specific mass percentages without introducing halides or metal nanoparticles. The synergistic effect of these three oxides with other components can form the spectral characteristics and color rendering properties of the glass, thereby enabling the use of photoinduced processes to achieve color rendering and obtain colored glass products with customized patterns or zoned colors.

[0012] Specifically, the mass percentage of Sb₂O₃ in the photoinduced oxide-doped glass of this application should be controlled to be 0.30%~0.50%. Sb₂O₃ acts as a thermal reducing agent; when no Sb₂O₃ is introduced or the mass percentage of Sb₂O₃ is too low, there is no absorption peak at 300 nm; when the mass percentage of Sb₂O₃ is ≥0.30%, an absorption peak can be induced; when the mass percentage of Sb₂O₃ is ≥0.50%, peak overlap occurs, and the absorption spectra tend to be consistent. That is, when the mass percentage of Sb₂O₃ is 0.50%, Sb₂O₃... 3+ The content of [something] reached the threshold.

[0013] The mass percentage of Ag₂O in the photoinduced oxide-doped glass of this application should be controlled to be 0.05%~0.30%. Ag₂O acts as a photosensitizer, and during the heat treatment stage... + A chemical reaction will occur: Ag + +e - →Ag 0 Thus transforming into Ag 0 Through the surface plasmon resonance (SPR) effect, Ag 0 The inherent frequency of Ag₂O can be matched with the frequency of a certain wavelength of light, thereby absorbing that wavelength and achieving color rendering. If the mass percentage of Ag₂O is too low, it will cause Ag… 0 If the content of Ag2O is too low, it will be difficult to achieve a color development effect; if the mass percentage of Ag2O is too high, it will lead to Ag... 0 The content of Ag is too high, and Ag 0 It is also a nucleating agent, and excessive content can lead to excessive crystal growth in the glass body, affecting the overall performance.

[0014] The mass percentage of CeO2 in the photoinduced oxide-doped glass of this application should be controlled to be 0.10%~0.30%. CeO2 acts as a photosensitizer, and during the melting stage, Ce... 4+ It will be reduced by Sb2O3 to generate Ce 3+ During the exposure phase, Ce 3+ Photoexcited electron transfer oxidation to Ce 4+ Ce 3+ +hν→[Ce 3+ →Ce 4+ +e - This allows for Ag + +e - →Ag 0 Provides electron support. If the mass percentage of CeO2 is too low, resulting in insufficient electron supply, Ag... 0 If the content is too low, or if the mass percentage of CeO2 is too high, it can easily lead to severe yellowing of the glass.

[0015] Furthermore, the mass percentages of SiO2, Al2O3, ZrO2, and alkali metal oxides in the photoinduced oxide-doped glass of this application can directly affect the intrinsic refractive index, network density, and silver ion migration rate of the glass, and indirectly regulate the particle size in the glass.

[0016] Specifically, the mass percentage of SiO2 in the photoinduced oxide-doped glass of this application should be controlled to be 70.00%~75.00%. SiO2, as a network structure forming agent within the glass, is the main structure of the glass and the glass after crystallization, and is also a major component constituting the crystalline phase. If the mass percentage of SiO2 is too low, it will make it difficult for the crystalline phase to form; if the mass percentage of SiO2 is too high, it will increase the high-temperature viscosity of the glass, causing melting difficulties.

[0017] The mass percentage of Al2O3 in the photoinduced oxide-doped glass of this application should be controlled to be 5.00%~8.00%. The introduction of Al2O3 can improve the strength of the glass structure, and enhance its scratch resistance and drop resistance. Simultaneously, the volume of Al2O3 in the glass structure is larger than that of silicon-oxygen tetrahedra, providing strengthening channels during chemical strengthening treatment and promoting ion strengthening. However, Al2O3 is a refractory oxide; if the mass percentage of Al2O3 is too high, it will significantly increase the high-temperature viscosity of the glass, reduce its fluidity, and affect its melting.

[0018] The alkali metal oxides R2O in the photoinduced oxide-doped glass of this application are mainly Li2O, Na2O, and K2O. These significantly reduce the high-temperature viscosity of the glass, promote melting and clarification, and significantly improve its fluidity. Furthermore, Li2O is an essential component of the crystalline phase; however, excessive Li2O can corrode mainstream production equipment such as platinum crucibles and industrial furnaces. Therefore, the mass percentage of Li2O should be controlled between 9.00% and 12.00%. Na2O is an important component of Na-K ion exchange during chemical strengthening treatment, which can create compressive stress on the glass surface, thereby increasing the glass's strength. However, excessive Na2O will reduce the glass's chemical stability; therefore, the mass percentage of Na2O should be controlled between 1.50% and 3.20%. K2O is a non-essential component; its introduction can increase the glass's coefficient of thermal expansion and improve its mechanical properties. Therefore, the mass percentage of K2O should be controlled between 0% and 4.00%.

[0019] The mass percentage of B2O3 in the photoinduced oxide-doped glass of this application should be controlled to be 0%~0.60%. Among them, B2O3 is a network-forming oxide and is a non-essential component. Its introduction can reduce the high-temperature viscosity of the glass and improve its melting characteristics. However, B2O3 is volatile, and excessive B2O3 can have adverse effects on the melting furnace and feed channel.

[0020] The mass percentage of ZrO2 in the photoinduced oxide-doped glass of this application should be controlled to be 3.00%~5.00%. ZrO2 is an essential component of photoinduced oxide-doped glass. Because photoinduced oxide-doped glass has a low overall viscosity and contains a large amount of Li2O, it is prone to crystallization, leading to defects. Introducing ZrO2 can suppress the crystallization ability of the glass, which is beneficial for shaping and avoiding defects. At the same time, ZrO2 can also improve the toughness of the glass. However, ZrO2 is a component that is extremely difficult to melt and is prone to deposition; therefore, its content should not be too high.

[0021] The mass percentage of P2O5 in the photoinduced oxide-doped glass of this application should be controlled to be 1.50%~2.50%. P2O5 serves as an auxiliary nucleating agent, due to its P... 5+ The high field strength of ions makes it easy for them to separate from the network and form crystal nuclei, which promotes phase separation in the glass, lowers the nucleation activation energy, and is conducive to the nucleation and growth of crystals in the glass.

[0022] In some embodiments, in the photoinduced oxide-doped glass, 0.07≤A=(Sb2O3+Ag2O+CeO2) / (Al2O3+ZrO2)≤0.11; wherein each oxide in the formula represents its mass percentage in the photoinduced oxide-doped glass.

[0023] For example, the ratio of A can be 0.07, 0.08, 0.09, 0.10, or 0.11, etc.

[0024] In this application, by controlling 0.07≤A=(Sb2O3+Ag2O+CeO2) / (Al2O3+ZrO2)≤0.11, yellow, red, brown, black, and mixed colors of glass can be achieved. If the ratio of A is too low, the photoinduced response is extremely weak, and there is no color change; if the ratio of A is too high, it is easy to cause the agglomeration of silver particles, resulting in the formation of variegated spots and poor stability.

[0025] In some embodiments, the photoinduced oxide-doped glass includes exposed and unexposed regions.

[0026] In some embodiments, the thickness of the photoinduced oxide-doped glass is 0.4 mm to 1.0 mm, for example, it can be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1.0 mm.

[0027] In some embodiments, the crystallinity of the exposed region of the photoinduced oxide-doped glass is ≥55%, for example, it can be 55%, 58%, 60%, 62%, 65%, 68%, or 70%, etc.

[0028] In some embodiments, the crystal phase of the exposure region of the photoinduced oxide-doped glass includes Li₂SiO₃, Li₂Si₂O₅, or LiAlSi₄O₃ crystal phases. 10 Any one or at least two of the crystal phases, typical but not limiting combinations include the combination of Li₂SiO₃ and Li₂Si₂O₅ crystal phases, and the combination of Li₂Si₂O₅ and LiAlSi₄O₃ crystal phases. 10 The combination of crystal phases, Li2SiO3 and LiAlSi4O 10 The combination of crystal phases: Li₂SiO₃, Li₂Si₂O₅, and LiAlSi₄O 10 Combinations of crystalline phases, etc.

[0029] In some embodiments, the color of the exposure area of ​​the photoinduced oxide-doped glass includes any one or a combination of at least two of yellow, red, brown, or black. Typical but non-limiting combinations include combinations of yellow and red, yellow and brown, red and brown, red and black, brown and black, yellow and black, etc.

[0030] In some embodiments, the crystallinity of the non-exposed region of the photoinduced oxide-doped glass is ≥50%, for example, it can be 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, or 70%, etc.

[0031] In some embodiments, the crystal phase of the non-exposed region of the photoinduced oxide-doped glass includes Li₂SiO₃, Li₂Si₂O₅, or LiAlSi₄O₃. 10 Any one or at least two of the crystal phases, typical but not limiting combinations include the combination of Li₂SiO₃ and Li₂Si₂O₅ crystal phases, and the combination of Li₂Si₂O₅ and LiAlSi₄O₃ crystal phases. 10 The combination of crystal phases, Li2SiO3 and LiAlSi4O 10 The combination of crystal phases: Li₂SiO₃, Li₂Si₂O₅, and LiAlSi₄O 10 Combinations of crystalline phases, etc.

[0032] In some embodiments, the non-exposed region of the photoinduced oxide-doped glass has a transmittance of ≥91% for visible light at a wavelength of 550 nm, for example, 91%, 91.2%, 91.5%, 91.8%, or 92%.

[0033] In some embodiments, the CS of the non-exposed region of the photoinduced oxide-doped glass is 240MPa to 350MPa, for example, it can be 240MPa, 260MPa, 280MPa, 300MPa, 320MPa, 340MPa or 350MPa.

[0034] In some embodiments, the CS-50 of the non-exposed region of the photoinduced oxide-doped glass is 130MPa to 180MPa, for example, it can be 130MPa, 140MPa, 150MPa, 160MPa, 170MPa or 180MPa, etc.

[0035] In this application, "CS" refers to the surface compressive stress value of the non-exposed area of ​​the photo-induced oxide-doped glass after chemical strengthening treatment, and "CS-50" refers to the compressive stress value from the surface to a depth of 50 μm in the non-exposed area of ​​the photo-induced oxide-doped glass after chemical strengthening treatment.

[0036] Secondly, this application provides a method for preparing photoinduced oxide-doped glass as described in the first aspect, comprising the following steps:

[0037] The raw materials for photoinduced oxide-doped glass are sequentially melted, shaped, annealed, and cut to obtain a glass substrate; the glass substrate is then exposed to obtain a photoinduced oxide-doped glass precursor; the photoinduced oxide-doped glass precursor is subsequently subjected to heat treatment and chemical strengthening treatment to obtain the photoinduced oxide-doped glass; the photoinduced oxide-doped glass comprises the following components by mass percentage: 70.00%~75.00% SiO2, 5.0%... 0%~8.00% Al2O3, 9.00%~12.00% Li2O, 1.50%~3.20% Na2O, 0%~4.00% K2O, 0%~0.60% B2O3, 3.00%~5.00% ZrO2, 1.50%~2.50% P2O5, 0.30%~0.50% Sb2O3, 0.05%~0.30% Ag2O and 0.10%~0.30% CeO2.

[0038] This application prepares a photoinduced oxide-doped glass with color-developing properties by introducing specific mass percentages of Sb₂O₃, Ag₂O, and CeO₂, inducing valence state transitions within the glass through exposure, and then subjecting it to heat treatment. Furthermore, through chemical strengthening treatment, the photoinduced oxide-doped glass can meet the performance requirements of the external components of portable electronic devices.

[0039] It should be noted that the operating parameters for the glass substrate preparation process in this application are not specifically required or limited, and those skilled in the art can make adaptive adjustments based on the specific composition and content of the raw materials.

[0040] In some embodiments, the melting temperature is 1350°C to 1500°C, for example, it can be 1350°C, 1400°C, 1450°C or 1500°C.

[0041] In some embodiments, the forming method includes any one or a combination of at least two of the following: casting, pull-down, or micro-float. Typical but non-limiting combinations include a combination of casting and pull-down, a combination of pull-down and micro-float, a combination of casting and micro-float, a combination of casting, pull-down, and micro-float, etc.

[0042] In some embodiments, the annealing temperature is 500°C to 600°C, for example, it can be 500°C, 520°C, 540°C, 550°C, 560°C, 580°C or 600°C.

[0043] In some embodiments, the light source for exposure includes a surface light source and / or a laser.

[0044] In some embodiments, the wavelength of the light source used for exposure is 300nm to 310nm, for example, it can be 300nm, 302nm, 304nm, 305nm, 306nm, 308nm or 310nm, etc.

[0045] In this application, a light source with a wavelength of 300nm~310nm is used, which can accurately and efficiently excite Ce. 3+ To Ce 4+ Transform and release electrons.

[0046] In some embodiments, the distance between the light source for exposure and the surface of the glass substrate is 30mm to 165mm, for example, it can be 30mm, 50mm, 80mm, 100mm, 125mm, 150mm or 165mm.

[0047] In some embodiments, the illumination intensity of the light source used for exposure is 0 mW / cm². 2 ~130mW / cm 2 And not 0mW / cm 2 For example, it could be 10mW / cm 2 20mW / cm 2 50mW / cm 2 80mW / cm 2 100mW / cm 2 Or 130mW / cm 2 wait.

[0048] In some embodiments, the exposure time is 10s to 30min, for example, it can be 10s, 30s, 1min, 5min, 10min, 15min, 20min, 25min or 30min, etc.

[0049] In some embodiments, the exposure is performed in conjunction with a light-shielding plate to selectively expose the glass substrate in sections.

[0050] This application allows for precise control of Ag by adjusting the distance to the light source, the light intensity, and the exposure time. + By adjusting the degree of color reproduction and nucleation density, and combining this with light-shielding plates of different patterns, not only can color rendering be achieved, but also various aesthetic effects such as zoned coloring and customized textures can be realized. The light intensity in the area blocked by the light-shielding plate is 0, and no photoinduced reaction occurs, thus maintaining the glass's original high light transmittance. If the light intensity is too low, the light source distance is too long, or the exposure time is too short, the photosensitive excitation is insufficient, resulting in inadequate color saturation. If the light intensity is too high, the light source distance is too short, or the exposure time is too long, the reaction rate is too fast or the reaction time is too long, easily leading to defects such as silver particle aggregation and blurred color boundaries.

[0051] In some embodiments, the heat treatment includes a first heat treatment and a second heat treatment performed sequentially.

[0052] In this application, the first heat treatment can stably grow and uniformly disperse the photoinduced silver crystal nuclei, avoiding particle agglomeration; the second heat treatment can control the final size and distribution state of the silver nanoparticles, while inducing the precipitation of lithium aluminum silicon microcrystalline phase in the proportional substrate, thereby simultaneously achieving color shaping and strengthening of glass mechanical properties.

[0053] In some embodiments, the chemical enhancement treatment includes a first chemical enhancement treatment and a second chemical enhancement treatment performed sequentially.

[0054] In some embodiments, the temperature of the first heat treatment is 480°C to 550°C, for example, it can be 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C.

[0055] In some embodiments, the heating rate of the first heat treatment is 1℃ / min to 10℃ / min, for example, it can be 1℃ / min, 2℃ / min, 5℃ / min, 8℃ / min or 10℃ / min.

[0056] In some embodiments, the holding time of the first heat treatment is 60 min to 180 min, for example, it can be 60 min, 90 min, 120 min, 150 min or 180 min.

[0057] In some embodiments, the temperature of the second heat treatment is 600°C to 720°C, for example, it can be 600°C, 620°C, 640°C, 660°C, 680°C, 700°C or 720°C.

[0058] In some embodiments, the heating rate of the second heat treatment is 1℃ / min to 5℃ / min, for example, it can be 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min or 5℃ / min, etc.

[0059] In some embodiments, the holding time of the second heat treatment is 30 min to 90 min, for example, it can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min.

[0060] In some embodiments, the bath salt for the first chemically enhanced treatment is a 100wt% NaNO3 bath salt.

[0061] In some embodiments, the temperature of the first chemical strengthening treatment is 440°C to 460°C, for example, it can be 440°C, 445°C, 450°C, 455°C or 460°C.

[0062] In some embodiments, the duration of the first chemical enhancement treatment is 4 to 6 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours, or 6 hours.

[0063] In some embodiments, the bath salt for the second chemically enhanced treatment is a 100 wt% KNO3 bath salt.

[0064] In some embodiments, the temperature of the second chemical strengthening treatment is 380°C to 440°C, for example, it can be 380°C, 390°C, 400°C, 410°C, 420°C, 430°C or 440°C.

[0065] In some embodiments, the second chemical enhancement treatment time is 20 min to 40 min, for example, it can be 20 min, 25 min, 30 min, 35 min or 40 min.

[0066] Thirdly, this application provides a color-developing glass article, which includes photo-induced oxide-doped glass as described in the first aspect; the color-developing glass article can be applied to the appearance components of portable electronic devices.

[0067] The numerical range described in this application includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values ​​included in the range.

[0068] Compared with the prior art, this application has the following advantages:

[0069] This application introduces Sb2O3, Ag2O, and CeO2 into photoinduced oxide-doped glass at specific mass percentages without introducing halides or metal nanoparticles. The synergistic effect of these three oxides with other components can form the spectral characteristics and color rendering properties of the glass, thereby enabling the use of photoinduced processes to achieve color rendering and obtain colored glass products with customized patterns or zoned colors.

[0070] Furthermore, the mass percentages of SiO2, Al2O3, ZrO2, and alkali metal oxides in the photoinduced oxide-doped glass of this application can directly affect the intrinsic refractive index, network density, and silver ion migration rate of the glass, and indirectly regulate the particle size in the glass. Attached Figure Description

[0071] Figure 1 This is an image of the photoinduced oxide-doped glass provided in Embodiment 2 of this application.

[0072] Figure 2 This is an image of the photoinduced oxide-doped glass provided in Embodiment 6 of this application.

[0073] Wherein, 1-unexposed area, 2-exposed area. Detailed Implementation

[0074] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.

[0075] The scope of this application can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form a valid range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this application. In addition, if the minimum range values ​​1 and 2 are listed, and the maximum range values ​​3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this application. In this application, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0076] Unless otherwise specified, the term "at least two combinations" in this application refers to a quantity greater than or equal to 2. For example, "any one or at least two combinations" means any one of the listed items, or a combination of at least two of the listed items in a manner that does not conflict and enables the implementation of this application.

[0077] In this application, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a set consisting of A, B, and combinations of A and B. "Including A and / or B" can be understood, depending on the context of the statement, as including A, including B, or including both A and B. In this application, "optional" means that the corresponding feature, component, step, or solution is not essential, i.e., selected from either "present" or "absent" parallel solutions. If multiple "optional" limitations appear in a technical solution, unless otherwise specified and without technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.

[0078] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond those listed. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A may consist only of a1, a2, and a3, or it may include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements."

[0079] All embodiments and optional embodiments of this application, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this application. The term "embodiment" mentioned in this application means that a specific feature, structure, or characteristic described in connection with an embodiment can be included in at least one embodiment or implementation of this application. The appearance of this phrase in various positions in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this application can be combined with other embodiments without technical conflict.

[0080] In this application, the ordinal numbers “first,” “second,” “third,” and “fourth” used in expressions such as “first aspect,” “second aspect,” “third aspect,” and “fourth aspect” are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.

[0081] In this application, the order in which the steps are written in the methods described in the various embodiments does not imply a strict execution order. The actual execution order of each step should be determined according to its function and possible internal logic. Unless otherwise specified, all steps in this application can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.

[0082] Example 1

[0083] This embodiment provides a photoinduced oxide-doped glass. The composition and mass percentage of the photoinduced oxide-doped glass and the ratio of A ((Sb2O3+Ag2O+CeO2) / (Al2O3+ZrO2)) are shown in Table 1.

[0084] The method for preparing photoinduced oxide-doped glass provided in this embodiment includes the following steps:

[0085] (1) Weigh the raw materials of photoinduced oxide doped glass according to the component formula shown in Table 1, mix them evenly and melt them at 1400℃ to obtain glass liquid; pour the glass liquid into the casting mold for molding by casting method; anneal at 550℃ and finally cut it into glass substrates of 38mm×38mm×0.7mm.

[0086] (2) Using a light-shielding plate with a specific pattern, selectively expose the glass substrate in sections to obtain a photoinduced oxide-doped glass precursor. The wavelength of the light source for selective exposure is 310 nm, the distance between the light source and the surface of the glass substrate is 100 mm, and the light intensity is 120 mW / cm². 2 Exposure time: 10 seconds.

[0087] (3) The photoinduced oxide-doped glass precursor was subjected to a first heat treatment, a second heat treatment, a first chemical strengthening treatment, and a second chemical strengthening treatment in sequence to obtain the photoinduced oxide-doped glass. The first heat treatment was performed at a temperature of 540℃, a heating rate of 5℃ / min, and a holding time of 90min; the second heat treatment was performed at a temperature of 705℃, a heating rate of 3℃ / min, and a holding time of 60min. The first chemical strengthening treatment used 100wt% NaNO3 bath salt, was performed at a temperature of 450℃, and was performed for 5h; the second chemical strengthening treatment used 100wt% KNO3 bath salt, was performed at a temperature of 420℃, and was performed for 30min.

[0088] Examples 2 to 8

[0089] Examples 2 to 8 each provide a photoinduced oxide-doped glass. The composition of the photoinduced oxide-doped glass, its mass percentage, and the ratio of A are shown in Table 1.

[0090] The preparation methods of photoinduced oxide-doped glass provided in Examples 2 to 8 are the same as in Example 1, except that in step (1), the raw materials of the photoinduced oxide-doped glass required for each are accurately weighed according to the component formula shown in Table 1, and the light intensity and exposure time in step (2) and the temperature and holding time of the first heat treatment and the second heat treatment in step (3) are adjusted accordingly. The specific adjustments are shown in Table 2.

[0091] Examples 9-10 and Comparative Examples 1-3

[0092] Examples 9-10 and Comparative Examples 1-3 each provide a photoinduced oxide-doped glass. The composition of the photoinduced oxide-doped glass and its mass percentage and the ratio of A are shown in Table 3.

[0093] The preparation methods of photoinduced oxide-doped glass provided in Examples 9-10 and Comparative Examples 1-3 are the same as those in Example 1, except that in step (1), the raw materials required for photoinduced oxide-doped glass are accurately weighed according to the component formula shown in Table 3.

[0094]

[0095]

[0096]

[0097] The following tests were performed on the photoinduced oxide-doped glasses provided in Examples 1-10 and Comparative Examples 1-3:

[0098] (1) Crystallinity and crystal phase of the exposed and unexposed areas respectively: XRD test was used to determine the crystal phase by comparing the XRD diffraction peaks with the database spectrum. The crystallinity was obtained by calculating the proportion of the diffraction intensity of the crystal phase in the overall spectrum intensity using the Rietveld method.

[0099] (2) The color of the exposed area.

[0100] (3) Transmittance of the non-exposed area in visible light at a wavelength of 550nm: measured using a UV-Vis spectrophotometer.

[0101] (4) CS and CS-50 in the non-exposed areas: tested using an SLP-2000 surface stress meter.

[0102] The test results are shown in Tables 4 and 5.

[0103]

[0104]

[0105] As shown in Tables 4 and 5, Examples 1 to 8 of this application introduce Sb₂O₃, Ag₂O, and CeO₂ into photoinduced oxide-doped glass at specific mass percentages. Their synergistic effect with other components shapes the spectral characteristics and color rendering of the glass. Through photoinduced reaction and heat treatment under specific conditions, photoinduced oxide-doped glass with customized patterns or zoned colors can be obtained, and the visible light transmittance in the non-exposed areas is high. Through chemical strengthening treatment, the CS and CS-50 of the photoinduced oxide-doped glass are also high. The images of the photoinduced oxide-doped glass provided in Examples 2 and 6 are shown below. Figure 1 and Figure 2 As shown.

[0106] Compared to Example 1, Examples 9 and 10 adjusted the mass percentage of certain components, making the ratio of A too high or too low. When the ratio of A is too high, it easily leads to the aggregation of silver particles. Therefore, the exposed area of ​​the photoinduced oxide-doped glass provided in Example 9 is yellow but has discolored spots. When the ratio of A is too low, the photoinduced response is extremely weak and there is no color change. Therefore, the exposed area of ​​the photoinduced oxide-doped glass provided in Example 10 has no obvious color change and remains transparent.

[0107] Compared to Example 1, the photoinduced oxide-doped glasses provided in Comparative Examples 1 to 3 do not include Sb₂O₃, Ag₂O, or CeO₂ in their composition. When Sb₂O₃ is not included, the lack of Sb₂O results in… 3+ For Ce 4+ →Ce 3+ The reduction-promoting effect prevents the formation of the corresponding Ce. 3+ This, in turn, affects Ag + Gain electrons and generate Ag 0 Nanoparticles, consequently, cause the exposed areas of the photoinduced oxide-doped glass to remain transparent without significant color change; when Ag₂O is not included, due to the absence of Ag… + Source: Unable to generate Ag 0 This leads to Ag 0 The color change caused by the surface plasmon resonance effect of nanoparticles fails, resulting in no significant color change and continued transparency in the exposed area of ​​the photoinduced oxide-doped glass; when CeO2 is not included, the loss of Ce... 3+ +hν→[Ce 3+ →Ce4 + +e - The effective ion that releases electrons, Ag + Unable to be reduced to Ag 0 This led to Ag 0 Nanoparticles cannot be generated, resulting in no significant color change in the exposed area of ​​the photoinduced oxide-doped glass, which remains transparent.

[0108] In summary, this application, without introducing halides and metal nanoparticles, introduces Sb2O3, Ag2O, and CeO2 into photoinduced oxide-doped glass at specific mass percentages. The synergistic effect of these three oxides with other components can form the spectral characteristics and color rendering properties of the glass, thereby enabling the use of photoinduced processes to achieve color rendering and obtain colored glass products with customized patterns or zoned colors.

[0109] Furthermore, the mass percentages of SiO2, Al2O3, ZrO2, and alkali metal oxides in the photoinduced oxide-doped glass of this application can directly affect the intrinsic refractive index, network density, and silver ion migration rate of the glass, and indirectly regulate the particle size in the glass.

[0110] The applicant declares that the above description is only a specific implementation of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application fall within the protection and disclosure scope of this application.

Claims

1. A photoinduced oxide-doped glass, characterized in that, The photoinduced oxide-doped glass comprises, by mass percentage, the following components: 70.00%~75.00% SiO2, 5.00%~8.00% Al2O3, 9.00%~12.00% Li2O, 1.50%~3.20% Na2O, 0%~4.00% K2O, 0%~0.60% B2O3, 3.00%~5.00% ZrO2, 1.50%~2.50% P2O5, 0.30%~0.50% Sb2O3, 0.05%~0.30% Ag2O, and 0.10%~0.30% CeO2.

2. The photoinduced oxide-doped glass according to claim 1, characterized in that, In the photoinduced oxide-doped glass, 0.07 ≤ A = (Sb₂O₃ + Ag₂O + CeO₂) / (Al₂O₃ + ZrO₂) ≤ 0.11; In the formula, each oxide represents its mass percentage in the photoinduced oxide-doped glass.

3. The photoinduced oxide-doped glass according to claim 1 or 2, characterized in that, The photo-induced oxide-doped glass includes an exposed region and a non-exposed region; And / or, the thickness of the photoinduced oxide-doped glass is 0.4 mm to 1.0 mm.

4. The photoinduced oxide-doped glass according to claim 3, characterized in that, The crystallinity of the exposed region of the photoinduced oxide-doped glass is ≥55%; And / or, the crystal phase of the exposure region of the photoinduced oxide-doped glass includes Li2SiO3, Li2Si2O5, or LiAlSi4O3 crystal phases. 10 Any one or at least two of the crystal phases; And / or, the color of the exposed area of ​​the photoinduced oxide-doped glass includes any one or a combination of at least two of yellow, red, brown or black; And / or, the crystallinity of the non-exposed region of the photoinduced oxide-doped glass is ≥50%; And / or, the crystal phase of the non-exposed region of the photoinduced oxide-doped glass includes Li2SiO3, Li2Si2O5, or LiAlSi4O3. 10 Any one or at least two of the crystal phases; And / or, the non-exposed region of the photoinduced oxide-doped glass has a transmittance of ≥91% for visible light at a wavelength of 550 nm; And / or, the CS of the non-exposed region of the photoinduced oxide-doped glass is 240MPa~350MPa; And / or, the CS-50 of the non-exposed region of the photoinduced oxide-doped glass is 130MPa~180MPa.

5. A method for preparing photoinduced oxide-doped glass as described in any one of claims 1 to 4, characterized in that, Includes the following steps: The raw materials for mixed photoinduced oxide-doped glass are sequentially melted, shaped, annealed, and cut to obtain a glass substrate; The glass substrate is exposed to obtain a photoinduced oxide-doped glass precursor; The photoinduced oxide-doped glass precursor was subjected to heat treatment and chemical strengthening treatment in sequence to obtain the photoinduced oxide-doped glass. The photoinduced oxide-doped glass comprises, by mass percentage, the following components: 70.00%~75.00% SiO2, 5.00%~8.00% Al2O3, 9.00%~12.00% Li2O, 1.50%~3.20% Na2O, 0%~4.00% K2O, 0%~0.60% B2O3, 3.00%~5.00% ZrO2, 1.50%~2.50% P2O5, 0.30%~0.50% Sb2O3, 0.05%~0.30% Ag2O, and 0.10%~0.30% CeO2.

6. The preparation method according to claim 5, characterized in that, The melting temperature is 1350℃~1500℃; And / or, the forming method includes any one or a combination of at least two of the following: casting, pull-down, or micro-float. And / or, the annealing temperature is 500℃~600℃.

7. The preparation method according to claim 5 or 6, characterized in that, The light source for the exposure includes a surface light source and / or a laser; And / or, the wavelength of the light source used for exposure is 300nm~310nm; And / or, the distance between the light source for exposure and the surface of the glass substrate is 30mm~165mm; And / or, the light intensity of the exposed light source is 0 mW / cm². 2 ~130mW / cm 2 And not 0mW / cm 2 ; And / or, the exposure time is 10s to 30min; And / or, the exposure is performed in conjunction with a light-shielding plate to selectively expose the glass substrate in designated areas.

8. The preparation method according to any one of claims 5 to 7, characterized in that, The heat treatment includes a first heat treatment and a second heat treatment performed sequentially. And / or, the chemical enhancement treatment includes a first chemical enhancement treatment and a second chemical enhancement treatment performed sequentially.

9. The preparation method according to claim 8, characterized in that, The temperature of the first heat treatment is 480℃~550℃; And / or, the heating rate of the first heat treatment is 1℃ / min to 10℃ / min; And / or, the holding time for the first heat treatment is 60 min to 180 min; And / or, the temperature of the second heat treatment is 600℃~720℃; And / or, the heating rate of the second heat treatment is 1℃ / min to 5℃ / min; And / or, the holding time for the second heat treatment is 30 min to 90 min; And / or, the bath salt for the first chemical enhancement treatment is 100 wt% NaNO3 bath salt; And / or, the temperature of the first chemical strengthening treatment is 440℃~460℃; And / or, the duration of the first chemical enhancement treatment is 4 to 6 hours; And / or, the bath salt for the second chemical enhancement treatment is 100 wt% KNO3 bath salt; And / or, the temperature of the second chemical strengthening treatment is 380℃~440℃; And / or, the duration of the second chemical enhancement treatment is 20 min to 40 min.

10. A color-developing glass product, characterized in that, The color-developing glass product includes the photo-induced oxide-doped glass as described in any one of claims 1 to 4; The colored glass products can be used for exterior components of portable electronic devices.

Citation Information

Patent Citations

  • Multicolored photosensitive glass-based parts and methods of manufacture

    CN109311732A

  • Colorful photosensitive microcrystalline glass as well as preparation method and application thereof

    CN120943529A